IMPLEMENTATION OF EXCELLENT SERVICE TO BANK SYARIAH INDONESIA (BSI) CUSTOMERS - Multazam. Darul Qutni; Eni Kusrini (Scholar Express Journals, 2023)
The application of Excellent Service to Bank Syariah Indonesia (BSI) customers is research that aims to identify, analyze and evaluate service strategies and practices that focus on service excellence within BSI. Bank Syariah Indonesia (BSI) is a financial institution that operates based on sharia principles, and its success in providing superior service to its customers has a significant impact on the reputation and growth of this bank. This study uses a qualitative approach by conducting in-depth interviews with various parties. those involved in BSI, including senior management, service staff and active customers. Apart from that, this research also explores related literature on service excellence in the context of sharia banking. The research results show that the implementation of Service Excellent at BSI is supported by several key factors, including management commitment to improving service, employee training and development, use of technology to improve service processes , and regular performance measurement. Apart from that, BSI also actively communicates with its customers to hear their feedback and continues to improve services based on this input. In conclusion, implementing Service Excellent for Bank Syariah Indonesia (BSI) customers is an important step in maintaining and increasing customer trust, expanding market share, and achieve sustainable growth. This study provides insights into best practices that can be adopted by other Islamic banks to improve the quality of their services and meet customer expectations in a competitive context.
Keywords: Excellent; Bank; Indonesia